Analysis Of The Conversion Of Agricultural Land To Non Agricultural Land In The Lereng Gunung Lawu Karanganyar Tourism Area (Case Study on Culinary Business) - Rahma Putri Divanti (Faculty of Law, Universitas Negeri Semarang, 2025)
This research discucces the phenomenon of conversion of agricultural land to non-agricultural land in the Lereng Gunung Lawu Tourism Area, Tawangmangu District, Karanganyar Regency. The purpose of this study is to analyze the factors causing land conversion and its impact on agriculture in the area. This research uses a qualitative method with an empirical legal approach, relying on primary data from interviews and observations, and secondary data from literature studies. The results of the research indicate that (1) land conversion is driven by complex interactions of economic, socio-cultural and environmental factors. Economically, the desire of land owners to gain more benefits than farming. Socio-culturally, in the form of changes in lifestyle and low interest of the younger generation to become farmers, and an environment that has geographical potential that supports tourism development. (2) The impact of land conversion because it is not a center for staple food production. However, there is a decrease in land productivity and changes in agricultural commodities to adjust to the demand for the tourism market. Land conversion increases the risk of flooding and erosion due to poor drainage and water absorption. The research emphasizes the importance of land management and the principles of sustainable development in the management of agricultural-based tourism areas on the slopes of Mount Lawu.